The role of sperm DNA fragmentation on male infertility in Al kut city - Othman Hashem Mohammed; Rania Sabri Hasan; Ghassan Jabbar Khalaf; Haidar Hussein Essa; Luma Hikmat Kareem; Wisam Basim Al- Tmemy; Zeena Mohammed Abdul Hassan (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Infertility is one of the most common diseases in the world in last period of all types,whether it is due to (asthenospermia,oligoasthenospermia,teratospermia,hormonal imbalance).Study aims to reveal negative effect of sperm DNA fragmentation on fertilization, this studywas conducted in the Al-Jazeera Specialized Laboratory in the city of Kut for the periodbetween (January to November from 2024), two hundred A person suffering from infertility.The semen was examined for all of them, they were divided into eighty of them being normal(the control group) and one hundred and twenty suffering from infertility (asthenospermia)hormonal test and sperm DNA fragmentation test (by Kit methods) was performed for everyone, this study showed Following, we obtained higher proportions of sperm DNA fragmentedinfertile Which had an abnormal shape and low motility. The results are similar to those ofother studies, which found that the DFI in infertile group was significantly higher than that infertile group (34.53 ± 4.6 % compared to11.91 ± 4.0 %) and mean sperm concentration infertile group was significantly higher compared to infertile group (83.22 ± 14.9 /ml comparedto11.67 ± 10.7 /ml) from this study. Through this study, the DFI test they can be used fordiscrimination and between the infertile male and normal male . Male men with sperm (DFI ≥25.1% ) had a (2.52 ) times higher risk of infertility compared to males with sperm (DFI <25.1%). This study shows that there is a negative relationship between (spem DNAfragmentation , sperm motility and formation) in infertile males. In addition, it can be concluded that sperm DNA fragmentation is very useful in selecting and choosing suitable sperm to beused in many techniques, including assisted reproductive techniques. It can also be concludedthat the results of sperm DNA fragmentation analysis are encouraging and useful and can beused for diagnostic purposes in determining male infertility